Addressing the employability of SMK students through improved English curriculum - Latasha Safira; Fatharani Taqisa Nadhira (Center for Indonesian Policy Studies (CIPS), 2022)
Compared to other education levels, Sekolah Menengah Kejuruan (SMK) graduates were the highest contributors (11.45%) to the unemployment rate in Indonesia in February 2021. Though worsened by the COVID-19 pandemic, this is largely due to the misalignment of skills being taught in school and industry needs. Employers struggle to find graduates that meet their required qualifications, especially for English competencies. Though SMK teachers and students generally perceive English competencies as an important skill, SMK graduates still do not meet the levels demanded by their industries. While a number of factors contribute to this problem, the overarching cause is the existing curriculum.
Keywords: 330